Antiferromagnetic Magnon Drag Effect and Giant On–Off Ratio in a Vertical Device. Issue 2 (15th January 2022) - Zhou, Yongjian; Guo, Tingwen; Liao, Liyang; Chen, Xianzhe; Han, Lei; Yin, Siqi; Qiao, Leilei; Huang, Lin; Zhou, Xiaofeng; Bai, Hua; Chen, Ruyi; Pan, Feng; et al.
Abstract: Antiferromagnets offer unique advantages in the development of spintronics because of the absence of stray field, insensitivity to external disturbances and the ultrafast terahertz eigenfrequency, advancing the development of devices toward small‐size and high‐speed. However, the ultralow read‐out signals of antiferromagnetic spintronics are notoriously smaller than their ferromagnetic counterpart, seriously hindering the development of antiferromagnets. Thus, experimental realization of large read‐out signals in antiferromagnets, especially in vertical devices, is intensely pursued. Here the antiferromagnetic magnon drag effect and a giant on–off ratio of ≈1000 are realized in a vertical sandwich structure of heavy metal/antiferromagnetic insulator/heavy metal (Pt/α‐Fe2 O3 /Pt). The read‐out signal can exist up to room temperature, and the detected signal owing to the transmission and blocking of magnon strongly relies on the relative orientation between spin polarization and Néel vector. Benefiting from the nonvolatile characteristic of Fe2 O3, zero‐field vertical magnon transport is achieved. The giant on–off signals in vertical devices that can be tightly packed, can greatly promote the practical application of antiferromagnetic magnon devices toward smaller, faster, and lower energy consumption. Abstract : A giant on–off ratio of ≈1000 is reported due to antiferromagnetic magnon drag effect in a vertical device Pt/α‐Fe2 O3 /Pt where signals are dependent on the orientation between spin polarization and Néel vector. In addition, the field‐free vertical magnon transport is obtained, resulting in nonvolatile signal. The results represent a significant step toward ultrahigh‐density integrated and energy‐saving antiferromagnetic spintronics/magnonics.